"A False Idea of Economy": Costs, Counties, and the Origins of the California Correctional System. Issue 1 (March 2016) - Ball, W. David
Realignment in California comes at a time when the state's prison system is expensive and overcrowded; the response has been to reevaluate and reconfigure the way counties use state prisons. Based on an original historical analysis of state archival records from the late nineteenth and early twentieth centuries, as a well as a review of secondary historical accounts of California's prison system, I show that similar problems and policies were present at the state's founding: issues of expense, overcrowding, and the county-state relationship help to explain the origins, size, and shape of the California prison system. California's lack of money first drove it to try to house prisoners on the cheap, starting when it made county jails the state prison system by fiat, continuing through a decade of privatization and convict lease arrangements in San Quentin, and concluding with a state-administered system partly funded by prison labor. By the time the value of prison labor atrophied and the true costs of a nonremunerative prison system revealed itself, the state was locked into fiscal and administrative responsibility for prisoners. Along the way, however, state and local governments sought to pass carceral responsibilities—and their attendant expenses—from one level of government to another in a manner that resembles today's battles over Realignment.